PEMBENTUKAN AKHLAK MELALUI PENDIDIKAN PONDOK PESANTREN DILIHAT DARI PERSPEKTIF PENDIDIKAN ISLAM DI INDONESIA - Fahmi, Apriliano; Yenti, Afrida; Rahmania, Fadilla; Hendrizal, Hendrizal (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research aims to explain the formation of morals through Islamic boarding school education from the perspective of Islamic education in Indonesia. The method used in this research is a qualitative method with a literature study approach. The results of this research show that Islamic boarding schools as the first educational institutions in Indonesia have given birth to many golden generations, Islamic boarding schools have written gold ink in the historical civilization of the Indonesian nation. Islamic boarding schools are not only institutions for seeking and studying knowledge but also places for character building in students. When they graduate from Islamic boarding schools, the students are expected to be able to apply knowledge and provide examples and role models for society. In this case, moral education through Islamic boarding schools is very successful in building morals in today's young generation.